Empagliflozin Contributes to Polyuria via Regulation of Sodium Transporters and Water Channels in Diabetic Rat Kidneys - Chung, Sungjin; Kim, Soojeong; Son, Mina; Kim, Minyoung; Koh, Eun Sil; Shin, Seok Joon; Ko, Seung-Hyun; Kim, Ho-Shik (Frontiers in Physiology, 2019)
Besides lowering glucose, empagliflozin, a selective sodium-glucose cotransporter-2 (SGLT2) inhibitor, have been known to provide cardiovascular and renal protection due to effects on diuresis and natriuresis. However, the natriuretic effect of SGLT2 inhibitors has been reported to be transient, and long-term data related to diuretic change are sparse. This study was performed to assess the renal effects of a 12-week treatment with empagliflozin (3 mg/kg) in diabetic OLETF rats by comparing it with other antihyperglycemic agents including lixisenatide (10 μg/kg), a glucagon-like peptide receptor-1 agonist, and voglibose (0.6 mg/kg), an α-glucosidase inhibitor. At 12 weeks of treatment, empagliflozin-treated diabetic rats produced still high urine volume and glycosuria, and showed significantly higher electrolyte-free water clearance than lixisenatide or voglibose-treated diabetic rats without significant change of serum sodium level and fractional excretion of sodium. In empagliflozin-treated rats, renal expression of Na+-Cl- cotransporter was unaltered, and expressions of Na+/H+ exchanger isoform 3, Na+-K+-2Cl- cotransporter, epithelial Na+ channel were decreased compared with control diabetic rats. Empagliflozin increased an expression of aquaporin (AQP)7 but did not affect AQP3 and AQP1 protein expressions in diabetic kidneys. Despite the increased expression in vasopressin V2 receptor, protein and mRNA levels of AQP2 in empagliflozin-treated diabetic kidneys were significantly decreased compared to control diabetic kidneys. In addition, empagliflozin resulted in the increased phosphorylation of AQP2 at S261 through the increased cyclin-dependent kinases 1 and 5 and protein phosphatase 2B. These results suggest that empagliflozin may contribute in part to polyuria via its regulation of AQP2 in diabetic kidneys.